Resilience & Reinvention: A Path for Management, It Social Sciences and Law: Role of Cyber Laws to Protect Intellectual Property Laws of the Nations - Chhaudha, Ishani Chhaudha1; Sharma, Aditi (Trinity Law Review, 2023)
This research paper revolves around the concept of intellectual property rights and how these rights are been allocated , this research paper ensures that the development of invention and to what extent and to which type of IPR can be use for a article created or an invention created , it ensures that there few provision and laws which not only help for the protection of the invention and the rights of the inventor , ensuring the role of cyber space and how the protection of the invention takes place , it helps in the development of the inventions and a stepping stone ensures the new edge in the creation of the new inventions and inventors , this research paper revolves around the few case laws and the criteria to get protected and enhancing the skills.